Options and Tradeoffs in Krabi's Coastal Land Use - Tipparat Pongthanapanich (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
This paper explores the tradeoff options for optimal coastal land use in Krabis coastal land development zone (CLDZ). Maximizing the net private benefit and maximizing the net environmental benefits, subject to the constraints set by land availability, effluent discharge from shrimp farms, and rice consumption are optimized via multiobjective programming. It is found that although the benefit from present land use pattern is close to the efficient level (Pareto frontier), reallocation of land use and revision of CLDZ are required in order to achieve an efficient outcome of planning. Designating aquaculture zones on the basis of carrying capacity is found to be an important scheme to control the impacts of shrimp farm discharges. The combined measures of carrying capacity and green taxation would lead to economically and environmentally responsible aquaculture. Compliance with aquaculture effluent standard alone could potentially lead to the detrimental optimum, and would be superfluous if aquaculture zones based on carrying capacity were designated.
Keywords: C61; D62; D74; Q24; 330; Coastal management; Pareto frontier; multiobjective programming; Krabi; Aquakultur; Krebstiere; Küstenregion; Ökosteuer; Pareto-Optimum; Thailand